Comparative toxicity of hydrocarbons for evaluation of Lysmata boggessi as an experimental proxy for deep-water column micronekton. (2022) - Renegar, D. Abigail; Turner, Nicholas R.; Bera, Gopal; Whitemiller, Eileen G.; Riegl, Bernhard M.; Sericano, José L.; Knap, Anthony
Abstract: The potential impacts of sub-surface hydrocarbon plumes to deep-water column micronekton are an important consideration in a more complete understanding of ecosystem effects resulting from deep-sea oil spills. However, evaluating toxicity in these organisms presents multiple challenges, and the use of a shallow-water proxy species allows comparison and validation of experimental results. This study thus examined the suitability of the peppermint shrimp, Lysmata boggessi, as an experimental proxy for ecologically important deep-sea zooplankton/micronekton in hydrocarbon toxicity assays. This crustacean species occurs in shallow coastal marine environments throughout the western Atlantic, Caribbean and Gulf of Mexico, is similar in size to the mesopelagic organisms previously tested and is readily available via commercial aquaculture. The effects of 1-methylnaphthalene and fresh Macondo oil (MC252) on L. boggessi were assessed in 48-h constant-exposure toxicity tests, and acute thresholds were compared to previously determined LC50s for oceanic mid water Euphausiidae, Janicella spinacauda, Systellaspis debilis, Sergestes sp., Sergia sp. and the mysid shrimp Americamysis bahia . Acute thresholds and the calculated critical target lipid body burden (CTLBB) for the shallow-water L. boggessi were comparable to the deep-water species tested, suggesting that L. boggessi may be a suitable proxy for some mesopelagic micronekton species in acute hydrocarbon exposures. Highlights: Acute endpoints for L. boggessi were comparable to mesopelagic crustaceans. CTLBBs for L. boggessi were similar to those determined for mesopelagic crustaceans. L. boggessi may be a suitable proxy for some micronekton in hydrocarbon exposures.